Dielectric and ferroelectric study of La5Ti4O15 synthesized by semi wet - Yadava S.S.; Khare A.; Gautam P.; Mandal K.D. (My University, 2025)
La5Ti4O15(LTO) ceramic was successfully synthesized by semi-wetroute. The Dielectric and ferroelectric properties of the LTO ceramic was compared at different temperatures and frequencies. The single phase formation of LTO ceramic was observed at 1400°C, which was confirmed by X-ray diffraction analysis. Scanning Electron Microscopy shows the presence of homogeneous grains while EDX analysis conﬁrmed the purity of the material. The PE hysteresis loop of LTO ceramic showstemperature dependent remnant polarization and coercive field. The electrical anddielectricproperties were studied with variation of temperature and frequency. The La5Ti4O15 has high dielectric constant (ɛ’ = 690)at 100Hz and 373K. © 2016, ICE Publishing. All rights reserved.